Pelaksanan Rekredensial Tenaga Keperawatan oleh Komite Keperawatan - Ria Agusnita; Doni Jepisa; Herman M Purwonegoro (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Implementation of nursing credentials through the nursing committee is currently influenced by the assessment of hospital accreditation standards by KARS or JCI. The Dumai General Hospital has not optimally carried out credentials, because since 2015 credentials have been carried out for First Clinical Nurses and First Practitioner Midwives, There has never been a credential to increase the career path of nurses and midwives. The purpose of this study was to apply the concepts and theories of hospital management to solve the problem of the nursing committee in the implementation of recredentials by the nursing committee. This study uses a qualitative method with a rapid assessment procedure research design. The technique of taking informants is purposive sampling, namely the key informant is the head of the nursing and the main informant is the chairman of the nursing committee. The data collection technique was carried out by in-depth interviews, document review and observation. Some of the problems found in the nursing committee unit by using the USG technique were obtained as priority problems for not implementing the recredentials which was caused by the non-establishment of the ad hoc committee, there are the differences in perception between the nursing committee and the ad hoc committee in determining the method of implementing the recredential, the procedure operational standards are not yet optimal and there is no specific budget for laboratory facilities and infrastructure. The Alternate problem solving can be used is a formulate an ad hoc committee, training for ad hoc committees, making policies, procedure operational standards, assessment tools and budget proposals for the implementation of nursing  recredentials.